Two-dimensional Few-circle Optical Pulses in the Inhomogeneous Environment of Carbon Nanotubes - M.B. Belonenko; I.S. Dvuzhilov; O.Yu. Tuzalina (Журнал нано- та електронної фізики)
We consider the task about few-circle optical pulses dynamics (light bullets) in the inhomogeneous environment of carbon nanotubes. Electromagnetic field of pulse describes classically, on basis of Maxwell equation, and carbon nanotubes give dispersion law for electrons, which interacting with pulse. We show that light bullets propagate stably.